Faktor-Faktor Yang Mempengaruhi Cash Holdings Pada Perusahaan Manufaktur Tahun 2017-2019 - Marlin Yang, Augustpaosa Nariman (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to determine the effect of cash flow volatility, liquidity, firm size, and leverage on cash holdings of manufacturing companies listed on the Indonesian Stock Exchange in 2017-2019. The samples used in this research were 87 manufacturing companies each year selected by purposive sampling technique. The instrument used to obtain secondary data was carried out by observing the financial statements of manufacturing companies listed on the Indonesian Stock Exchange in 2017-2019. The analytical method used is multiple regression analysis with EViews program. The results of this research indicate firm size has a positive effect on cash holdings and liquidity has a negative effect on cash holdings. While cash flow volatility and leverage have no effect on cash holdings.